The scaffold protein p62 regulates adaptive thermogenesis through ATF2 nuclear target activation - Katrin Fischer (Nature Portfolio, 2020)
Beta-adrenergic stimulation of brown adipose tissue leads to thermogenesis via the activating transcription factor 2 (ATF2) mediated expression of the thermogenic genes Ucp1 and Pgc-1α. Here, the authors show that the scaffold protein p62 regulates brown adipose tissue function through modifying ATF2 genomic binding and subsequent Ucp1 and Pgc-1α induction.